Miras bırakanın muvazaalı işlemleri - Sevgi, Emre (My University, 2008)
MİRAS BIRAKANIN MUVAZAALI İŞLEMLERİ Muvazaa, tarafların üçüncü şahısları aldatmak amacıyla görünürde yaptıkları hukuki işlemin hiç hüküm doğurmaması veya görünürdeki işlemden başka bir işlemin hükümlerini doğurması yönündeki anlaşmalarıdır. Miras bırakanın mirasçılarından mal kaçırmak amacıyla muvazaalı işlem yapması durumunda ortaya çıkan, Türk Hukuku’nda büyük yeri ve önemi olan miras bırakanın muvazaası her zaman güncelliğini koruyan bir konudur. Miras bırakan yasa hükümleri ve toplumun değer yargılarına rağmen mirasçıları arasında eşitliği bozan, mirasçılarının hepsinin veya bir kısmının zararına olacak tasarruflarda bulunmakta, bağış arzusunu satımla gizlemekte, satım işlemi muvazaalı olarak geçersiz olduğu için yapılan işlemler iptal edilmektedir. Miras bırakanın muvazaası nitelikli muvazaa türündendir. Nitelikli muvazaada görünürdeki işlem muvazaa nedeniyle geçersizdir. Gizli işlem ise kural olarak geçerlidir. Kural olarak diyoruz çünkü, gizli işlemin geçerli sayılması için kanunda o işlem için öngörülen bir şekil varsa o şekle uyulmuş olması, konusunun hukuka veya ahlaka aykırı olmaması gerekir. Miras bırakanın muvazaalı işlemlerinden uygulamada en sık rastlananı miras bırakanın tapulu taşınmazını gerçekte bağışladığı halde görünürde tapuda satış veya ölünceye kadar bakma sözleşmesiyle devrettiği işlemlerdir. Doktrinde tapuda görünürdeki işlemde şekle uyulmakla gizlenen bağışlama sözleşmesinin şekle aykırılığının ileri sürülemeyeceği yönünde görüş bulunmakla birlikte, Yargıtay istikrar kazanmış içtihatlarıyla görünürdeki işlemin muvazaalı, gizli işlemin de şekle aykırı olması nedeniyle geçersiz olduğunu kabul etmiştir. Yine doktrinde gizli bağışlama sözleşmesinin mirasçıların miras haklarını bertaraf etmeye yönelik olduğu için hileli anlaşma (Kollusion) niteliğinde BK m.19 ve 20 uyarınca ahlaka aykırı olduğu yönünde çalışmamızda savunduğumuz görüş bulunmaktadır.

FICTITIOUS TRANSACTIONS OF TESTATORS Fictitious transactions are the agreements in the direction that the legal transactions that parties do create no judgment at all or no judgments are created from another transaction done ostensibly for the purpose of misleading third persons. Testator’s fictitious transaction which has a great place in Turkish law is a subject which always protects its actuality in the case when testator makes fictitious transactions for the purpose of cheating his/ her inheritors. In spite of the provisions of law giving legacy and other judgments of the public, they alter the equality between the inheritors, make dispositions that will be at the loss of all or some of the inheritors, hid selling desire with donation, and the transactions made are cancelled as selling transactions have been executed fictitiously. Falsification of testator is of high quality type of falsification. Ostensible transaction in good quality falsification is invalid because of falsification. And secret transaction is valid as rule. We say “as rule”, because in order to make the secret transaction to be considered valid, if there is a form planned in the law for making that transaction to be valid, than that should be observed, its subject shouldn’t be against the law and ethics. The most frequently encountered fictitious transactions of testators in application are the transactions by which testators transfer the registered immovable property by the agreement ensuring that they will be looked after until they die in spite of the fact that in reality they have donated. In the doctrine, however there is an opinion that no disagreement could be put forward on contradiction of donation agreement against the form in the ostensible transaction in register, Court of Appeal, has accepted by its ruling cases that ostensible transaction was invalid as it was fictitious, and the secret transaction was invalid as it was against the form. Also, in the doctrine, since the secret donation agreement is done for the purpose of eliminating inheritance rights of the inheritors, it is in the nature of collusion, there is an opinion in our studies which we defended in the direction that it is against the ethics in accordance with article 19 and 20 of Law of Obligations.
Keywords: Hukuk; Miras_Hukuk; Özel Hukuk